Study of the mechanical properties of mortars based on organic binders used in the reproduction of outdoor artworks - Alba Cerezo; Xavier Mas-Barber; Stéphane Kröner (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This work focuses on the characterization of organic resin bound mortars, used in reproductions of sculptural and ornamental stone exposed outdoors. The specimens were prepared from two commonly used organic binders in the scope of Culture Heritage Conservation/ Restoration, natural aggregates of crushed Tosca Rocafort limestone and three different additives. All the mortar specimens prepared were subjected to accelerated aging tests with UV irradiation, and then subjected to a 2kn tensile tester Deben microtest and SEM, in order to quantify the resistance and cracking stress.